KARAKTERISTIK TOKOH-TOKOH PEREMPUAN DALAM KUMPULAN CERPEN DUA WANOJA KARYA CHYE RETTY ISNENDES (KAJIAN PSIKOLOGI SASTRA) - Rismawati, Rismawati; Triwahyuni, Heti (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2017)
This reaserch has been held to describe the characteristics of female figures that contained at “Dua Wanoja” short story collection in terms of psychological side, the psychological condition of the author when making the character, and the relation between them. The method used on this research is dscriptive analytic method, while the data was obtaind from documentation, study analysis of data and inteview. 16 characteristics of 16 figures that mostly have a rebellious nature and exalt their egos was obtained from this research. It was evidenced by the emergence percentage data structure of personalities that 47% use the ego to satisfy 35.6% the urge id and only17.4% the involvement of the superego. Corespondingly,the author also exalt the ego, which is used 53.8% ego to satisfy 34.7% boost the by only involving used 11.5% superego. Considering two previous conclusions, so it is clear that the psychological condition of the author effects the psychological of the characters that created by her, it is also expressed on the relation between authors desire and her works that shown on 10 short stories studied, which is 50% short stories using the way condensation, 30% stories using method of symbolism and 20% using the way to move. The study support the opinion that the literature is the psychiatric product of the author is proven true.